1999
DOI: 10.1111/j.1748-0361.1999.tb00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural Health Research: Rural Hospitals and the Local Economy: A Needed Extension and Refinement of Existing Empirical Research

Abstract: The relationship between the health care sector and the rural economy is of increasing importance. Much additional research is needed to fully understand this relationship and to address some of the limitations of the modest amount of research that already exists. In this study, data from Nebraska were used to create a four-part typology of rural hospitals. Input-output analysis was used to assess the economic effects of each type of hospital on the local economy and to simulate the effects of three different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 4 publications
0
12
0
1
Order By: Relevance
“…Similar conclusions were reached using data from three Texas communities (Doeksen, Loewen, and Strawn 1990). Cordes et al (1999) extended the literature by examining the role of the hospital in the economy and differentiating hospitals by bed size. They found that the estimated economic multipliers increased in magnitude with hospital bed size, but did not specifically estimate the effect of closure using I/O analysis.…”
mentioning
confidence: 99%
“…Similar conclusions were reached using data from three Texas communities (Doeksen, Loewen, and Strawn 1990). Cordes et al (1999) extended the literature by examining the role of the hospital in the economy and differentiating hospitals by bed size. They found that the estimated economic multipliers increased in magnitude with hospital bed size, but did not specifically estimate the effect of closure using I/O analysis.…”
mentioning
confidence: 99%
“…Loss of general surgical care for trauma and common surgical emergencies could result in worse outcomes in more rural areas. In addition, the loss of revenue from general surgery may threaten the financial viability of struggling rural hospitals, with significant health and economic implications for the local community (Cordes, et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…˳êàðí³ òðåòüîãî ð³âíÿ ìîaeóòü áóòè ÿê çàãàëüíîãî ïðîô³ëþ (îáºäíóâàòè ïåâíó ê³ëüê³ñòü ñïåö³àëüíîñòåé), òàê ³ ñïåö³àë³çîâàí³ (îáñëóãîâóâàòè òó ÷è ³íøó ãðóïó íàñåëåííÿ, ñïåö³àë³çóâàòèñÿ íà òèõ ÷è ³íøèõ çàõâîðþâàííÿõ ÷è ìåòîäàõ ë³êóâàííÿ) [34;39]. Áàãàòî àâòîð³â âèêëþ÷í³ñòü âêàçàíèõ ôóíêö³é ë³êàðåíü òðåòèííîãî ð³âíÿ ñòàâëÿòü ï³ä ñóìí³â [50].…”
Section: îãëßä íàóêîâî¯ ë²òåðàòóðèunclassified